Community Empowerment in Utilizing Local Agricultural Waste as an Effort to Recover The Red Onion Farming Economy: Pemberdayaan Masyarakat dalam Memanfaatkan Limbah Lokal Pertanian sebagai Upaya Pemulihan Perekonomian Usahatani Bawang Merah - Irmayani Irmayani; Arman Arman; Nur Ilmi; Masnur Masnur (Universitas Lancang Kuning, 2023)
Enrekang Regency is the largest shallot producing area in South Sulawesi. The spread of shallot cultivation is found in several sub-districts in Enrekang Regency, especially in several sub-districts, especially in Baraka Sub-District, Banti Village, which is the largest producer of shallot commodities. Shallots require intense agricultural inputs so that farmers often insist on using chemicals in controlling pests and plant diseases that attack them, of course this has a very bad impact on the health of farmers and the environmental ecosystem, especially the shallot commodity itself which is cultivated is unhealthy for consumption because it contains dangerous heavy metals. Even though around the brand there are many agricultural wastes that are simply wasted and not utilized. These agricultural wastes can be processed into good organic fertilizer for plant growth and land rehabilitation. So that this community service aims to train shallot farmers to process and utilize agricultural waste that is around them to be used as good organic fertilizer for plant growth in the long term. This service activity was carried out with the partners of the Keinnawa Farmers Group in Baraka Village to increase awareness, concern, insight, skills and expertise in processing useful agricultural waste. The number of farmers involved is 55 people with community education, outreach, direct practice and mentoring methods. The results of this dedication resulted in the level of participation of farmers to be involved by 83% in activities and increased awareness of utilizing waste by 77%. The results obtained need to be continuously improved, especially the involvement of government officials to collaborate with academics to get assistance with Keinnawa Partners in maintaining the continuity of this activity.